Can emergency avoidance behavior reduce injuries to electric two-wheeler riders in vehicle collisions?. (3rd October 2022) - Pan, Di; Han, Yong; Wu, He; Lin, Liya; Wang, Bingyu; Huang, Hongwu
Abstract: Objectives: The aim of this study was to examine the effects of emergency avoidance behaviors on the kinematics and injuries of electric two-wheeler (ETW) riders. Methods: Four typical riding postures of ETW riders before collisions, including one normal posture and three avoidance postures, were identified through analysis of 298 videos of vehicle to ETW accidents. Crash simulations were then performed using the Total Human Model of Safety (THUMS) occupant model, ETW and a sedan finite element (FE) model, and the kinematics of ETW riders were compared. The risk of head injury and lower extremity injury was also investigated. Results: When the struck foot position of the ETW rider was lower than the ETW pedal, the lower extremity was struck by the sedan bumper and ETW frame from the right and left side respectively, and the upper body of the rider rotated around the hood leading edge. At a car velocity of 40 km/h, the rider was at high risk of head injury and the tibia was fractured. The medial cruciate ligament (MCL) was ruptured in both the 20 km/h and 40 km/h collisions. When the struck foot position of the ETW rider was higher than the pedal, the lower extremity was hit by the bumper and then rebounded. In this situation, the bending moments of the femur and tibia, as well as the bending angle and shear displacement of the knee joint were less than the injury threshold in all crash simulations. Furthermore, when the head was turned toward the colliding car, the risk of head injury varied with the emergency avoidance posture. Conclusions: The height of the struck foot relative to the ETW pedal influenced the rider's global kinematics, and head and lower extremity injuries risk. In the struck side foot landing and both feet landing postures, the lower extremity was restrained and compressed by the ETW frame, resulting in a high risk of tibia fracture and MCL rupture. Reducing the impact velocities could effectively mitigate the injury risk of the ETW riders; however, loading patterns remain an important factor influencing the risk of lower extremity injury.